»…since 1742« – en glasarkeologisk undersökning i Kosta - Åstrand, Johan (Hikuin, 2010)
»...since 1742« – a glassarchaeological investigation in Kosta By Johan Åstrand The Kosta glassfactory in Småland was founded in 1742 and is today Swedens oldest glass-industry still producing hand-blown glass. In 2006 a trial excavation was carried out on the place where the factory was located from the start until 1838. Even if the excavation was limited it is one of the few archaeological projects on 1800-century glassfactories in Scandinavia. The remains of the old factory were in large parts wellpreserved. Floorlevels from the old factory were preserved and contained waste from the glassblowing. A dump was situated outside the old factory where broken moulds and parts of furnaces had been thrown. Glassherds from various types of vessels were found and two glass-seals of a formerly unknown type with the factory’s signature K-S were found. One of the glass-furnaces that was unearthed was constructed in a different way than what is known about other furnaces in Kosta and Småland. It shows close similarity to a furnace that has been excavated in Åvik, Finland. The glass-factory in Åvik was founded in 1748 and the production was started by two wellkown glassblowers Fromm and Waltzer who had both been employed at Kosta. From 1750 we know that another type of furnace was introduced in Kosta. Maybe the uncovered »oldfashioned« furnace had been constructed by the two masters. The trial excavation in Kosta shows that even if there are rich historical sources, the accounts of the Kosta factory are preserved from 1742 until today, very little is known about how the 1800-century glassproduction was carried out. The archaeological knowledge about glassproduction is important for the interpretation of glass in a social context. It also gives opportunities to understand how the specialised knowledge of artisans was passed on in an early-industrial era.